From fish to fiber: 3D-nanoprinted optical neuromast for multi-integrated underwater detection - Liangye Li; Xuhao Fan; Geng Chen; Yueqi Liu; Fujun Zhang; Zhuolin Chen; Zhi Zhang; Wangyang Xu; Shixiong Zhang; Yuncheng Liu; Zongjing Li; Hui Gao; et al. (Nature Communications)
Abstract Fish possess high sensitivity to acoustic, vibrational, and hydrodynamic stimuli through unique sensing cells, providing unparalleled paradigms for developing underwater detection methods. However, artificial perception devices face challenges in replicating comparable sensitivity and multi-dimensional integration of fish in function and scale. Here, we propose a biomimetic optical fiber neuromast (BOFN) by leveraging synergistic optical-mechanical interactions for multifunctional underwater detection and communication. A heterogeneous integration technology for BOFN is developed based on sequential femtosecond laser direct writing with deposition, resulting in both compact size and reliable stability. Benefiting from its biomimetic design, BOFN demonstrates performance benchmarks in acoustic sensitivity of 172.24 V/kPa and marine turbulence sensitivity of 8560.72 nm/(m/s). A prototype system integrated into a motorized fish shows versatile acoustic sensing, target imaging, and underwater communication capabilities. Our work opens avenues for deploying all-optical bionic sensing cells in underwater environments, with promising applications in marine resource exploration and ecosystem protection.